Student-Athletes as Peer Counselors - Whitner, Phillip A.; Sanz, Donald L. (My University, 1988)
An innovative pilot project of peer counselors is implemented within the structure of an educational support service. Student-athletes helping other student-athletes to adjust and adapt to the rigors of a college environment is reported. The rationale for utilizing student-athletes as peer counselors, the measures taken to control the disadvantages which have been reported to be associated with their use, the pilot project's outcome, and recommendations for future use of student-athletes as peer counselors in educational support services are included. Five athletes (three women and two men) signed up to be peer counrselors, but ultimately, the pilot project failed.
Keywords: pilot; peer programs; transitions; freshmen